Copper-aluminum composite belt and preparation method thereof

By optimizing the content of copper base element in the copper-aluminum composite belt and adopting fine processes, the problems of unstable hardness, uneven interface and insufficient metallurgical bonding during the composite process of the copper-aluminum composite belt are solved, and the hardness, uniform interface and bonding strength are achieved. Improved effect.

CN119457010APending Publication Date: 2025-02-18CHINALCO DAYE COPPER PLATE & STRIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411522943.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the composite process, the existing copper-aluminum composite belts have problems such as unstable copper hardness, uneven bonding interface thickness and insufficient metallurgical bonding, which affects its performance.

Method used

By optimizing the Fe, P, Sn and Ni element content in the copper base layer in the copper-aluminum composite belt, and combining high-purity aluminum materials, fine surface treatment, degassing and impurity removal of aluminum liquid, heat treatment and high-temperature casting and rolling processes are used to ensure that High-efficiency metallurgical combination between copper and aluminum.

Benefits of technology

The hardness stability of the copper-aluminum composite belt, the uniform distribution of the bonding interface and the improvement of metallurgical bonding strength are achieved, and the layered cracking defects of the composite belt during stamping are avoided, and the lithium battery pole, automobile radiator and other fields are met. need.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005108435690000211
    Figure BDA0005108435690000211
  • Figure BDA0005108435690000221
    Figure BDA0005108435690000221
Patent Text Reader

Abstract

The invention relates to the technical field of copper material processing, and particularly provides a copper-aluminum composite belt and a preparation method thereof, the copper material comprises the following chemical components: 10-30 ppm of Fe, 10-30 ppm of P, 15-30 ppm of Sn, 10-20 ppm of Ni, and the balance of copper; the aluminum material comprises the following chemical components in percentage by weight: 99.0 to 99.9 percent of Al and the balance of inevitable impurities. The content of Fe + P is 20-50 ppm, and the content of Fe + P + Ni + Sn is 45-85 ppm. The strip is subjected to copper material surface treatment and aluminum material smelting; treating molten aluminum; carrying out copper-aluminum cast-rolling compounding; performing heat treatment on the composite strip; the copper-aluminum composite material which is stable in copper hardness, uniform in bonding interface and excellent in metallurgical bonding is obtained through the steps of cold rolling, cleaning treatment and the like, and the requirements of lithium battery pole columns, automobile radiators, solar heat collectors, ship manufacturing and the like are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper material processing, and in particular to a copper-aluminum composite strip and a preparation method thereof. Background Art

[0002] Copper-aluminum composite strips have the advantages of copper's high electrical conductivity, excellent thermal conductivity, low contact resistance, and aluminum's light weight, corrosion resistance, and economy, and are widely used in building installations, power electronics, equipment heat dissipation, chemical industry, military industry, etc. In view of the current situation of my country's scarcity of copper resources and serious overcapacity of aluminum production, "replacing copper with aluminum" has become one of the effective ways to resolve the overcapacity of aluminum and save precious metals.

[0003] Solid-liquid casting and rolling composite forming technology is a new short-process technology. It feeds the solid-phase coated metal strip and the liquid matrix metal into the two crystallization rollers of the twin-roll casting and rolling machine at the same time. After rapid solidification, it is directly cast and rolled under high temperature and pressure to obtain a copper-aluminum composite strip. However, during the composite process, there will be problems such as unstable copper material hardness, uneven thickness of the bonding interface, and insufficient metallurgical bonding resulting in weak bonding, which seriously affects the subsequent performance of the copper-aluminum composite strip. Based on this, how to improve the bonding performance of the copper-aluminum composite strip has become one of the technical problems that need to be solved urgently in this field. Summary of the invention

[0004] In view of this, the present invention provides a copper-aluminum composite strip and a preparation method thereof, which ensures that the copper-aluminum composite strip undergoes metallurgical bonding while both the copper material and the aluminum material have stable properties.

[0005] To achieve the above-mentioned purpose, the first aspect of the present invention provides a copper-aluminum composite strip, which includes a composite copper base layer and an aluminum base layer, wherein the copper base layer is composed of the following elements in weight percentage: 10-30 ppm of Fe, 10-30 ppm of P, 15-30 ppm of Sn, 10-20 ppm of Ni and the remainder of Cu; the aluminum base layer is composed of the following elements in weight percentage: 99.0-99.9% of Al and the remainder of inevitable impurities.

[0006] In some embodiments, the sum of the contents of Fe and P is 20-50 ppm, and the sum of the contents of Fe, P, Ni and Sn is 45-85 ppm.

[0007] The second aspect of the present invention also provides a method for preparing the above copper-aluminum composite strip, comprising the following steps:

[0008] Step 1: The copper strip is sequentially subjected to alkaline washing to remove oil and acid washing to remove the oxide layer to obtain a copper strip with a fresh surface for use; the aluminum material is smelted and heat-insulated to obtain aluminum liquid;

[0009] Step 2, the aluminum liquid is sequentially degassed by a graphite rotor and impurities are removed by a plate filter, and then sent to a casting nozzle through a flow channel to obtain aluminum liquid to be used;

[0010] Step 3: preheat the aluminum liquid and the copper strip to be used, and feed them into the roll gap of the twin-roll casting machine at the same time, and obtain the copper-aluminum composite strip billet under the action of high-temperature solid-liquid combination and rolling;

[0011] Step 4: placing the copper-aluminum composite strip blank in a vacuum atmosphere protection furnace for annealing to obtain an annealed copper-aluminum composite strip;

[0012] Step 5: cold rolling the annealed copper-aluminum composite strip on a cold rolling mill, followed by degreasing and oil removal, acid removal of the oxide layer, and grinding to obtain a finished copper-aluminum composite strip.

[0013] In some embodiments, in step 1, the thickness of the copper strip is 2.8-3.8 mm, and the Vickers hardness of the copper strip is 64-70 Hv.

[0014] In some embodiments, in step 1, the aluminum material is smelted at a temperature of 700-750°C and held at a temperature of 680-700°C.

[0015] In some embodiments, in step 2, the rotation speed of the graphite rotor is 60-80 rpm, and / or; the degassing gas introduced into the graphite rotor is argon, and / or; the pore size of the plate filter is 30-50 ppi.

[0016] In some embodiments, in step three, the preheating temperature of the copper strip is 350-400°C, and / or; the temperature of the aluminum material in the casting and rolling zone is 550-600°C, and / or; the billet discharge temperature is 260-280°C.

[0017] In some embodiments, in step three, the casting reduction is 15-25%, and the casting speed is 2.5-3.5 m / min.

[0018] In some embodiments, in step three, the Vickers hardness of the copper side of the copper-aluminum composite strip is 100-110 Hv.

[0019] In some embodiments, in step 4, the heating temperature of the copper-aluminum composite strip is 190-240° C., and the holding time is 2-4 hours.

[0020] In some embodiments, in step five, the annealed copper-aluminum composite strip is cold rolled six times, with a total deformation of 39-50%, and a single-pass deformation of 8-11%.

[0021] In some embodiments, the peel strength of the finished copper-aluminum composite strip is 35-40 N / mm.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention controls the content of Fe, P, Sn and Ni in the copper material in the copper-aluminum composite strip within a specific range, and controls the content of the alloy element combination to achieve a specific synergistic effect between the alloy elements, not only ensuring that the copper strip has sufficient hardness and sufficient bonding strength when the copper-aluminum composite strip is combined; at the same time, through the optimization of the composite process, the uniform distribution of the bonding interface of the copper-aluminum composite strip and the improvement of the bonding strength are ensured, so that the composite strip does not have delamination and cracking defects during the stamping process, so that it can meet the needs of lithium battery poles, automobile radiators, solar collectors and shipbuilding. Compared with the prior art, the method has the characteristics of stable copper material hardness, uniform bonding interface and excellent metallurgical bonding. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0026] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0027] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0028] In the existing process, although the solid-liquid casting and rolling composite forming technology has the advantages of short process flow and high efficiency, it still has some unavoidable technical challenges. For example, there is a temperature gradient difference between the solid copper strip and the liquid aluminum during the bonding process. If the temperature control of the copper strip and the aluminum liquid is uneven, or the cooling during the casting and rolling process is uneven, the thickness of the bonding interface will be uneven. The uneven fluidity, flow rate and flow direction of the aluminum liquid will lead to inconsistent thickness of the aluminum liquid covering the surface of the copper strip. The uneven distribution of aluminum liquid during the casting process will directly affect the thickness of the bonding interface. During the casting and rolling process, if the rolling pressure applied is uneven or the speed fluctuates, the copper strip and the aluminum liquid will be unevenly stressed when bonding, forming a bonding interface of uneven thickness. The surface cleanliness and flatness of the copper strip will also affect the spreading and bonding of the aluminum liquid on the copper strip. If there is an oxide layer or impurities on the surface of the copper strip, the aluminum liquid will be hindered during bonding, resulting in uneven interface thickness and the presence of inclusions. A certain metallurgical bond needs to be formed between copper and aluminum. However, during the casting and rolling process, improper process control of time, temperature, pressure, etc. will also lead to insufficient metallurgical bonding. If the thickness and distribution of the alloy layer are uneven, it may affect the bonding strength. The reaction rates between solid copper and liquid aluminum are different. If they are not properly controlled, the generation rate of the reaction layer may not match, affecting the metallurgical bonding. During the casting and rolling process, the composite strip will produce thermal stress and residual stress. These stresses are concentrated at the bonding interface, which may lead to a weak metallurgical bond.

[0029] The present invention optimizes the element composition and content of the copper base layer in the copper-aluminum composite strip. Combined with high-purity aluminum materials, the hardness stability, thickness uniformity of the bonding interface and metallurgical bonding strength of the copper-aluminum composite strip are optimized. The synergistic effect of these elements in copper not only improves the mechanical properties and surface chemical properties of the copper material, but also enhances the metallurgical bonding effect between copper and aluminum, thereby effectively overcoming the deficiencies in the prior art and improving the overall performance of the composite strip. Among them:

[0030] Iron (Fe) forms a solid solution in copper as a trace element. Trace amounts of iron can refine copper grains and improve the strength and hardness of copper materials. The solid solubility of iron in copper is extremely low, so it is easy to form fine second-phase particles, which work together with elements such as P and Sn to improve the strength and hardness of copper.

[0031] Phosphorus (P) forms Fe-P compounds with iron, further refining the grain structure. At the same time, phosphorus also helps the oxidation resistance of copper materials and helps reduce the formation of oxides. Phosphorus and iron work together to refine the grains and improve the oxidation resistance of copper, which helps to maintain the stability of hardness during high-temperature rolling.

[0032] Tin (Sn) can significantly increase the strength and hardness of copper and improve its corrosion resistance. Tin combines with iron, phosphorus, etc. to improve the mechanical properties and oxidation resistance of copper, so that the copper strip still maintains a stable hardness at high temperatures, which helps to improve the uneven thickness of the bonding interface.

[0033] Nickel (Ni) can improve the strength and hardness of copper, and increase its high temperature stability and corrosion resistance. Nickel works together with iron, phosphorus and tin to improve the hardness of copper, especially under high temperature conditions, to maintain the stability of hardness, to ensure that the hardness of copper does not fluctuate due to high temperature during the casting and rolling process, and to reduce the problem of uneven interface.

[0034] By controlling the content of iron, phosphorus, tin and nickel in the range of 10-30ppm, 10-30ppm, 15-30ppm and 10-20ppm respectively, the copper material is ensured to be refined in grains under high temperature conditions, the fluidity and flatness of the metal are improved, and the uniformity of the solid-liquid interface is optimized. The synergistic effect of the above elements improves the wettability of the copper surface and the spreadability of the aluminum liquid, reducing the uneven thickness of the interface. The refined grain structure and enhanced high-temperature stability ensure that the liquid aluminum can be evenly spread and combined with the copper material.

[0035] The above-mentioned iron, phosphorus, tin, and nickel elements will form certain alloy compounds in copper, which will improve the surface chemical activity of copper and enhance the metallurgical bonding of the copper and aluminum interface. The refined grains and improved oxidation resistance formed by iron and phosphorus, combined with the improved surface chemical activity of tin and nickel, promote the spreading and metallurgical reaction of aluminum on the copper surface, ensuring the formation of a strong bonding layer at the interface. The combination of elements optimizes the atomic diffusion and alloy layer formation at the interface between copper and aluminum liquid, and improves the overall bonding strength.

[0036] The reasonable proportion of iron, phosphorus, tin and nickel elements synergizes to improve the hardness stability of copper materials, especially under high temperature conditions, reducing the fluctuation of hardness and ensuring the uniformity of the overall performance of the composite strip. The addition of phosphorus improves the oxidation resistance of copper materials, reduces the formation of oxide layers during casting and rolling, and helps the metallurgical bonding of the interface.

[0037] Nickel and tin enhance the copper's resistance to softening at high temperatures, allowing the copper to maintain a high strength during the casting and rolling process, avoiding the softening of the copper due to high temperatures. Through the synergistic effect of various elements, the copper can still maintain good mechanical properties and chemical stability during the high-temperature composite process, ensuring the quality of the composite strip.

[0038] In summary, the synergistic effect of the elements Fe, P, Sn, and Ni optimizes the grain structure and surface properties of the copper material, improves the hardness and stability of the copper material, and ensures the uniformity of the bonding interface.

[0039] Through the synergistic effect of elements, the grains are optimized, wettability and surface chemical activity are improved, ensuring that the aluminum liquid can be evenly spread on the surface of the copper strip to form a good bonding interface.

[0040] Element control promotes the metallurgical reaction, ensures the effective diffusion of atoms at the interface and the formation of the alloy layer, improves the bonding strength, and solves the problem of weak metallurgical bonding.

[0041] As preferred element content parameters, the sum of the contents of Fe and P is 20-50 ppm, and the sum of the contents of Fe, P, Ni and Sn is 45-85 ppm.

[0042] Another aspect of the present invention provides a method for preparing the copper-aluminum composite strip, comprising the following steps:

[0043] S1, sequentially subjecting the copper strip to alkaline washing for oil removal and pickling for oxide layer removal to obtain a copper strip with a fresh surface for standby use; smelting and heat-insulating the aluminum material to obtain aluminum liquid;

[0044] S2, the aluminum liquid is sequentially degassed by a graphite rotor and impurities are removed by a plate filter, and then sent to a casting nozzle through a flow channel to obtain a filtrate to be used;

[0045] S3, preheating the aluminum liquid and the copper strip to be used, and feeding them into the roll gap of the twin-roll casting machine at the same time, and obtaining the copper-aluminum composite strip billet under the action of high-temperature solid-liquid combination and rolling;

[0046] S4, placing the copper-aluminum composite strip blank in a vacuum atmosphere protection furnace for annealing to obtain an annealed copper-aluminum composite strip;

[0047] S5. Cold rolling the annealed copper-aluminum composite strip on a cold rolling mill, followed by degreasing and oil removal, acid removal of the oxide layer, and grinding to obtain a finished copper-aluminum composite strip.

[0048] This technical solution ensures efficient bonding between copper and aluminum through fine surface treatment, degassing and impurity removal of aluminum liquid, heat treatment, and high-temperature casting and rolling.

[0049] The high-temperature solid-liquid bonding during the casting and rolling process and the subsequent annealing treatment ensure the uniformity of the thickness of the bonding interface. The optimization of each step, such as annealing to release stress, cold rolling to adjust the size, surface treatment, etc., ensures the stability of the mechanical properties of the composite strip. The solid-liquid casting and rolling process simplifies the production process of traditional composite materials, improves production efficiency and reduces production costs.

[0050] Furthermore, in step S1, the thickness of the copper strip is 2.8-3.8 mm, and the Vickers hardness of the copper strip is 64-70 Hv.

[0051] This technical solution uses a copper strip with optimized thickness and hardness, which not only provides good thermal conductivity and structural support, but also has sufficient mechanical strength and plastic deformation capacity at high temperatures, so that copper and aluminum can be fully combined during the casting and rolling process to form a uniform bonding interface. By controlling the thickness and hardness of the copper strip, the heat capacity and stress distribution of the copper strip during the casting and rolling process can be adjusted, reducing the problems of uneven thickness of the bonding interface and weak metallurgical bonding caused by temperature gradients and mechanical stress. By controlling the thickness and hardness of the copper material, surface defects can be effectively reduced and mechanical properties can be improved during the casting and subsequent cooling, annealing, and cold rolling processes, ensuring that the composite strip has good hardness, strength, and surface finish.

[0052] Furthermore, in step S1, the aluminum material is smelted at a temperature of 700-750°C and held at a temperature of 680-700°C.

[0053] This technical solution adopts optimized melting temperature and holding temperature, optimizes the quality and fluidity of aluminum liquid, promotes the efficient combination of aluminum liquid and copper strip during casting and rolling, and improves the comprehensive performance of copper-aluminum composite strip. In the range of 700-750℃, the aluminum material is completely melted and reaches a fluid state, which helps the impurities and gases in the aluminum liquid to float up, facilitating the subsequent degassing and impurity removal. This temperature range can effectively reduce the viscosity of aluminum liquid, enhance its fluidity, make it easier to separate and remove gas and solid impurities under gravity and convection, and improve the purity of aluminum liquid. Control of melting temperature helps to reduce oxidation reactions on the surface and inside of aluminum liquid, thereby reducing the formation of oxides. Melting temperature within this range can reduce the oxidation reaction rate when aluminum liquid contacts air, reduce the formation of aluminum oxide and other oxides, improve the purity of aluminum liquid, and avoid the formation of inclusions during the combination process. This temperature range ensures that the aluminum liquid can be fully and evenly heated and mixed during the melting process, reducing local overheating or overcooling caused by temperature gradients. Uniform melting temperature helps to form aluminum liquid with uniform temperature distribution, avoid uneven flow caused by local temperature difference during casting and rolling, and ensure that aluminum liquid can evenly coat the surface of copper strip. Control of holding temperature ensures that aluminum liquid can maintain stable temperature and composition before casting and rolling, and prevents composition segregation or air absorption caused by temperature change. Holding temperature in the range of 680-700℃ can effectively maintain the uniformity and stability of aluminum liquid, reduce alloy element segregation and air absorption caused by temperature fluctuation, and ensure the stability of aluminum liquid composition. Holding temperature prevents aluminum liquid from solidifying prematurely before being fed into the casting and rolling mill, thereby ensuring that aluminum liquid can flow smoothly and combine with copper strip. In the range of 680-700℃, aluminum liquid is still in a completely liquid state and has good fluidity, avoiding flow obstruction caused by premature solidification, and ensuring smooth flow and filling of aluminum liquid during casting and rolling. Appropriate holding temperature provides good temperature conditions for the solid-liquid combination of aluminum liquid and copper strip, and enhances the metallurgical bonding strength of the bonding interface. This temperature range enables the aluminum liquid and the copper strip to maintain good wettability and diffusivity when in high-temperature contact, promotes the diffusion and bonding of copper and aluminum atoms at the interface, and improves the strength of metallurgical bonding. The aluminum melting temperature is set at 700-750℃, and the holding temperature is 680-700℃, which helps to improve the purity, fluidity, composition stability and quality of the aluminum liquid's bonding interface. These temperature parameters overcome the problems of uneven thickness of the bonding interface and insufficient metallurgical bonding strength existing in the prior art by optimizing the physical and chemical properties of the aluminum liquid and the operating conditions during the casting and rolling process, and improve the mechanical properties, conductivity and service life of the copper-aluminum composite strip.

[0054] Furthermore, in step S2, the rotation speed of the graphite rotor is 60-80 rpm, and / or; the degassing gas introduced into the graphite rotor is argon, and / or; the pore size of the plate filter is 30-50 ppi.

[0055] The technical solution adopts a suitable graphite rotor speed and selects argon as the degassing gas, and sets the pore size of the plate filter, which is crucial for the purification and quality improvement of aluminum liquid. These operating parameters help to remove gas and solid impurities in aluminum liquid, optimize the purity and fluidity of aluminum liquid, and ensure that aluminum liquid can form a good bonding interface with copper strip. In the speed range of 60-80rpm, the graphite rotor can effectively introduce argon into aluminum liquid, forming tiny bubbles and improving the degassing effect in aluminum liquid. Moderate speed can generate sufficient shear force to promote argon to disperse in aluminum liquid and form a large number of tiny bubbles. When these bubbles rise, they can take away dissolved gas (such as hydrogen) in aluminum liquid, improving degassing efficiency. The speed of 60-80rpm can not only provide effective degassing stirring, but also avoid uneven stirring of aluminum liquid and excessive bubble rupture caused by too high speed. Too high speed will cause bubbles to rupture quickly, reduce the degassing effect, and may cause local temperature fluctuations and uneven flow of aluminum liquid. The speed of 60-80rpm can balance effective degassing and uniform stirring, so that aluminum liquid maintains stable fluidity. Moderate rotation speed can effectively reduce the exposure time of the aluminum liquid surface, reduce the oxidation reaction rate, and reduce the generation of oxidized inclusions. Too high rotation speed will aggravate the exposure of the aluminum liquid surface and increase the risk of oxidation and air inhalation; while the rotation speed of 60-80rpm can effectively stir the aluminum liquid while controlling the generation of oxidized inclusions and improving the purity of the aluminum liquid. The filter pore size of 30-50ppi can effectively filter out fine solid particles in the aluminum liquid and improve the purity of the aluminum liquid. The moderate pore size can intercept smaller solid impurities while ensuring the fluidity of the aluminum liquid, so that when the aluminum liquid passes through the filter, the solid impurities are effectively intercepted and the pure aluminum liquid can flow out smoothly. The pore size setting of 30-50ppi ensures that the aluminum liquid can maintain good fluidity during the filtration process and avoids flow obstruction caused by too small pores. Too small pores will cause the filter to be blocked, which will hinder the flow of aluminum liquid; too large pores may not be able to effectively intercept fine impurities. The pore size of 30-50ppi provides a good balance, which can effectively filter and maintain fluidity. Setting the pore size within the range of 30-50ppi helps reduce clogging during the filtration process, ensures that the aluminum liquid can pass through the filter continuously and stably, and improves production efficiency and filtration effect. By controlling the speed of the graphite rotor (60-80rpm), using argon for degassing, and setting the pore size of the plate filter (30-50ppi), the purity of the aluminum liquid can be significantly improved, and the fluidity and composition stability of the aluminum liquid can be optimized. These measures effectively solve the problem of gas and solid impurities in the aluminum liquid during the casting and rolling process, improve the bonding interface quality and metallurgical bonding strength of the copper-aluminum composite strip, and thus improve the comprehensive performance and service life of the composite strip.

[0056] Furthermore, in step S3, the preheating temperature of the copper strip is 350-400°C, and / or; the temperature of the aluminum material in the casting and rolling zone is 550-600°C, and / or; the billet discharge temperature is 260-280°C.

[0057] The precise control of the preheating temperature of the copper strip, the temperature of the aluminum material in the casting and rolling zone, and the billet temperature in this technical solution has a key impact on the quality and performance of the copper-aluminum composite strip. The setting of these temperature parameters can optimize the heat exchange and physical and chemical reactions during the casting and rolling process, ensure the good combination of copper and aluminum, and improve the comprehensive performance of the composite strip. By preheating the copper strip (350-400℃) and controlling the temperature of the aluminum liquid (550-600℃), the wettability of the copper-aluminum interface can be improved, so that the aluminum liquid can be more evenly coated and spread on the copper strip to form a uniform bonding interface. Reasonable control of the preheating temperature and the aluminum material temperature in the casting and rolling zone enhances the diffusion and mutual bonding of atoms at the copper-aluminum interface, reduces the pores and inclusions at the bonding interface, and improves the metallurgical bonding strength. The appropriate casting and rolling zone temperature (550-600℃) maintains the good fluidity of the aluminum liquid, ensures its uniform spreading on the surface of the copper strip, reduces the uneven thickness problem at the bonding interface, and improves the quality of the bonding interface. Controlling the billet temperature (260-280℃) helps maintain the uniformity of the composite strip, reduce flow obstacles and structural defects at the interface caused by temperature changes, and ensure the stability of the bonding interface. Appropriate preheating and casting temperature settings promote the metallurgical bonding of the copper-aluminum interface, reduce delamination and cracking at the interface, and improve the overall mechanical properties and metallurgical bonding strength of the composite strip. Controlling the billet temperature enables the composite strip to maintain good plasticity and machinability during subsequent processing such as cold rolling, improves the efficiency and quality of the composite strip in subsequent processing, and reduces quality problems that may occur during processing. The precise control of these temperature parameters significantly improves the bonding quality, metallurgical bonding strength and subsequent processing performance of the copper-aluminum composite strip, thereby overcoming the problems of unstable copper hardness, uneven thickness of the bonding interface, and insufficient metallurgical bonding strength in the prior art, and improving the overall performance and service life of the copper-aluminum composite strip.

[0058] Furthermore, in step S3, the casting reduction is 15-25%, and the casting speed is 2.5-3.5 m / min.

[0059] This technical solution sets the casting reduction to 15-25% and the casting speed to 2.5-3.5m / min. These parameters optimize the forming process of the copper-aluminum composite strip, ensure good mechanical bonding and metallurgical bonding, and improve the overall quality of the composite strip. The casting reduction is in the range of 15-25%, providing sufficient pressure to promote the metallurgical bonding between copper and aluminum, while maintaining the flatness and continuity of the interface. The moderate reduction can ensure that copper and aluminum are fully in contact at high temperatures. The oxide layer at the copper-aluminum interface is destroyed by compression, which increases the contact area of ​​the two metals, promotes the diffusion and bonding between atoms, and forms a strong metallurgical bonding interface. The control of the reduction helps to ensure that the thickness of the composite strip is within a stable range, reduce the problem of uneven thickness, and improve the uniformity of the finished strip. At a reduction of 15-25%, the casting mill can effectively control the thickness of the copper-aluminum composite strip, so that the copper-aluminum interface is uniform across the entire width, reduce the thickness fluctuation at the interface, and ensure that the finished strip has consistent mechanical properties and conductive properties. Moderate reduction reduces the residual stress inside the composite strip, avoiding defects and cracking caused by stress concentration in subsequent processing. During the casting process, the reduction is controlled at 15-25% to evenly distribute the internal stress, avoid interface cracking and delamination caused by stress concentration, and improve the mechanical strength and stability of the composite strip. The casting speed is in the range of 2.5-3.5m / min, which can provide appropriate forming time to form a stable bond between the copper and aluminum interfaces and ensure the quality of the composite strip. Within this speed range, the aluminum liquid and the copper strip can fully contact in the twin-roll casting mill, ensuring that the aluminum liquid spreads and solidifies evenly on the surface of the copper strip, reducing interface defects caused by too short or too long forming time. Appropriate casting speed helps to maintain uniform heat exchange between the copper strip and the aluminum liquid, avoid temperature gradient changes caused by too fast or too slow, and ensure the stability of the interface bonding. The casting speed is controlled at 2.5-3.5m / min so that the aluminum liquid can quickly cool and solidify on the surface of the copper strip, reducing interface defects caused by temperature gradients and improving the uniformity and stability of the bonding interface. When the speed is controlled within this range, the friction and tensile force generated during the casting and rolling process are kept within a reasonable range, reducing surface defects such as wrinkling, cracks and burrs, and improving the appearance quality and mechanical properties of the composite strip. The appropriate casting and rolling reduction (15-25%) and casting and rolling speed (2.5-3.5m / min) cooperate with each other to provide sufficient pressure and time, promote the metallurgical bonding of the copper-aluminum interface, make the interface bonding of the composite strip more firm, and reduce the interface peeling and delamination caused by weak bonding. The control of the reduction can accurately adjust the thickness of the composite strip, and the optimization of the speed ensures the uniform solidification and spreading of the aluminum liquid on the surface of the copper strip, reduces the uneven thickness at the interface, and improves the quality consistency of the composite strip. Moderate reduction and speed control reduce the residual stress inside the composite strip, avoid interface cracks and defects caused by stress concentration, and improve the mechanical strength and durability of the composite strip.By controlling the casting speed, the generation of defects on the surface of the composite strip can be reduced. At the same time, controlling the reduction can reduce internal defects, improve the overall quality of the composite strip, and make it more reliable in subsequent processing and use. The appropriate reduction and casting speed provide sufficient deformation and forming time, making the internal structure of the copper-aluminum composite strip more compact, improving the mechanical strength and toughness of the finished strip, and ensuring its stable performance in various application scenarios. Controlling the reduction and speed can optimize the metallurgical bonding of the copper-aluminum interface, reduce pores and impurities at the interface, improve the conductivity and corrosion resistance of the composite strip, and ensure its application performance in power electronics and equipment heat dissipation. The reasonable setting of these parameters can effectively overcome the problems of unstable copper hardness, uneven thickness of the bonding interface, and insufficient metallurgical bonding strength in the prior art, and significantly improve the overall performance and application value of the copper-aluminum composite strip.

[0060] Furthermore, in step S3, the Vickers hardness of the copper side of the copper-aluminum composite strip is 100-110 Hv.

[0061] This technical solution controls the Vickers hardness of the copper side of the copper-aluminum composite strip blank to 100-110Hv. By ensuring that the hardness of the copper material is moderate, the metallurgical bonding strength between copper and aluminum is optimized, the interface defects and uneven thickness problems are reduced, and the mechanical properties and processing performance of the composite strip are enhanced. This hardness range effectively overcomes the problems of unstable copper material hardness and insufficient metallurgical bonding strength in the existing process, and improves the overall quality and application performance of the copper-aluminum composite strip. The Vickers hardness of the copper side of the above-mentioned copper-aluminum composite strip blank is mainly determined by the temperature parameter control in the aforementioned process.

[0062] Furthermore, in step S4, the heating temperature of the copper-aluminum composite strip is 190-240° C., and the insulation time is 2-4 hours.

[0063] The purpose of this technical solution is to optimize the microstructure and properties of the composite strip through annealing treatment. Selecting this temperature range and holding time has the following advantages, which helps to improve the mechanical properties, stability and metallurgical bonding strength of the composite strip. The heating temperature of 190-240℃ can cause element diffusion at the interface within the copper-aluminum composite strip, further improving the metallurgical bonding strength. In this temperature range, the atomic activity of copper and aluminum intensifies, but does not cause melting or excessive alloying. Heating can promote the mutual diffusion between atoms at the interface and improve the metallurgical bonding strength of the bonding interface. The annealing temperature of 190-240℃ can effectively release the residual stress of the composite strip during the casting and rolling process, avoiding stress concentration problems in subsequent processing and use. Heating to this temperature range can activate the stress release mechanism inside the material, adjust the position of atoms in the lattice, evenly distribute stress, and reduce cracking and deformation caused by stress concentration. Through a holding time of 2-4 hours, the heating effect is evenly transmitted, improving the consistency of the material. Moderate annealing temperature and holding time can reduce the hardness of the material, increase plasticity and toughness, improve the deformation ability of the composite strip during mechanical processing, and reduce the fracture and damage caused by insufficient plastic deformation. The fatigue resistance of the material under dynamic load can be improved by annealing. The control of heating temperature and holding time can eliminate internal defects and stress concentration, improve the fatigue life of the material, and adapt to the dynamic load environment. The hardness of the composite strip after annealing is moderate, which is convenient for subsequent cold rolling processing, and improves processing accuracy and surface quality. Annealing in the range of 190-240℃ can reduce the hardness of the composite strip to an appropriate range, reduce the occurrence of fracture and surface defects during cold rolling, and improve cold rolling efficiency and quality. The optimization of annealing temperature and holding time enables the composite strip to have good ductility during the forming process, can effectively resist external stress, and reduce the cracking and delamination of the material during shearing and stamping. The heating temperature of 190-240℃ and the holding time of 2-4 hours in step S4 optimize the performance of the copper-aluminum composite strip through annealing. This temperature and time setting ensures the residual stress release and bonding interface enhancement of the composite strip, while improving the mechanical properties and processing performance of the composite strip. Reasonable annealing treatment can effectively overcome the problems of stress concentration, uneven interface thickness and insufficient bonding strength in the existing process, and improve the overall quality and application performance of the copper-aluminum composite strip.

[0064] Furthermore, in step S5, the annealed copper-aluminum composite strip is cold-rolled for 6 times, with a total deformation of 39-50%, and a single-pass deformation controlled at 8-11%.

[0065] This technical solution optimizes the mechanical properties, surface quality and processing performance of the composite strip. Reasonable cold rolling deformation and pass design help reduce stress concentration and surface defects, and improve the consistency and quality of the composite strip. By applying appropriate deformation amounts one by one, the strength and hardness of the material can be improved while maintaining good ductility and toughness, ensuring the stability and reliability of the composite strip in subsequent processing and applications.

[0066] Furthermore, the peel strength of the finished copper-aluminum composite strip is 35-40N / mm.

[0067] In the above process, through the optimization of alloy elements, careful control of surface treatment, optimization of solid-liquid casting and rolling process, and reasonable setting of cold rolling and annealing treatment, the peel strength of the finished copper-aluminum composite strip reached 35-40N / mm. This result not only reflects the excellent interface bonding strength of the composite strip, but also shows that it has good comprehensive mechanical properties and stability. High peel strength can ensure the reliability and service life of the composite strip in various applications, and provide a solid foundation for its application in lithium battery poles, automobile radiators and other fields.

[0068] The technical effects of the present invention are described below in conjunction with specific examples. In the following examples and comparative examples, the aluminum materials used are the same, and the aluminum content is 99.5%.

[0069] Example 1

[0070] The composition of the copper-aluminum composite material of this embodiment is shown in Table 1, and the performance test results are shown in Table 2, which are as follows:

[0071] S1: alkaline washing and oil removal of the copper strip, and then pickling to remove the surface oxide layer, to obtain a fresh surface standby copper strip, the standby copper strip has a thickness of 2.8 mm and a Vickers hardness of 70 Hv; the aluminum material is smelted and heat-insulated, the smelting temperature is 700 ° C, the heat-insulating temperature is 680 ° C, and the smelting qualified aluminum liquid is obtained;

[0072] S2: The aluminum liquid with qualified composition is sequentially degassed by a graphite rotor and impurities are removed by a plate filter, and then sent to the casting nozzle through a flow channel. The speed of the graphite rotor is 70r / min, the degassing gas introduced is argon, and the pore size of the plate filter is 50ppi, so as to obtain aluminum liquid with qualified composition;

[0073] S3: Preheat the aluminum liquid with qualified composition and the fresh copper strip on the surface to be used, the preheating temperature is 350°C, and feed them into the roll gap of the twin-roll casting and rolling machine at the same time. Through the high-temperature solid-liquid combination and rolling action, the aluminum material temperature in the casting and rolling zone is 600°C, the billet temperature is 280°C, the casting and rolling reduction is 15%, and the casting and rolling speed is 2.8m / min, so as to obtain a copper-aluminum composite strip billet with a Vickers hardness of 103Hv;

[0074] S4: placing the copper-aluminum composite strip blank in a vacuum protective atmosphere furnace for annealing at a heating temperature of 240° C. for a holding time of 2 h to obtain an annealed copper-aluminum composite strip;

[0075] S5: cold rolling the annealed copper-aluminum composite strip on a cold rolling mill, with 6 cold rolling passes, a total deformation of 39%, and a single pass deformation controlled at 8%, followed by degreasing and oil removal, acid removal of the oxide layer, and grinding to obtain a finished copper-aluminum composite strip.

[0076] Example 2

[0077] The composition of the copper-aluminum composite material of this embodiment is shown in Table 1, and the performance test results are shown in Table 2, which are as follows:

[0078] S1: The copper strip is alkaline washed to remove oil, and then pickled to remove the surface oxide layer to obtain a fresh surface copper strip for use, the thickness of the copper strip is 2.8 mm, and the Vickers hardness is 68 Hv; the aluminum material is smelted and heat-insulated, the smelting temperature is 720°C, and the heat-insulating temperature is 690°C, and a qualified aluminum liquid is obtained;

[0079] S2: The aluminum liquid with qualified composition is sequentially degassed by a graphite rotor and impurities are removed by a plate filter, and then sent to the casting nozzle through a flow channel. The speed of the graphite rotor is 75r / min, the degassing gas introduced is argon, and the pore size of the plate filter is 45ppi, so as to obtain aluminum liquid with qualified composition;

[0080] S3: Preheat the aluminum liquid with qualified composition and the fresh copper strip on the surface to be used at 400°C, and feed them into the roll gap of the twin-roll casting and rolling mill at the same time. Through high-temperature solid-liquid combination and rolling, the aluminum material temperature in the casting and rolling zone is 580°C, the billet temperature is 268°C, the casting and rolling reduction is 22%, and the casting and rolling speed is 3.5m / min, so as to obtain a copper-aluminum composite strip billet with a Vickers hardness of 100Hv.

[0081] S4: placing the copper-aluminum composite strip blank in a vacuum protective atmosphere furnace for annealing at a heating temperature of 220° C. for a holding time of 3 h to obtain an annealed copper-aluminum composite strip;

[0082] S5: cold rolling the annealed copper-aluminum composite strip on a cold rolling mill, with 6 cold rolling passes, a total deformation of 50%, and a single pass deformation controlled at 11%, followed by degreasing and oil removal, acid removal of the oxide layer, and grinding to obtain a finished copper-aluminum composite strip.

[0083] Example 3

[0084] The composition of the copper-aluminum composite material of this embodiment is shown in Table 1, and the performance test results are shown in Table 2, which are as follows:

[0085] S1: The copper strip is alkaline washed to remove oil, and then pickled to remove the surface oxide layer to obtain a fresh surface copper strip for use, the thickness of the copper strip is 3.8 mm, and the Vickers hardness is 64 Hv; the aluminum material is smelted and heat-insulated, the smelting temperature is 750°C, and the heat-insulating temperature is 700°C, and the smelting qualified aluminum liquid is obtained;

[0086] S2: The aluminum liquid with qualified composition is sequentially degassed by a graphite rotor and impurities are removed by a plate filter, and then sent to the casting nozzle through a flow channel. The speed of the graphite rotor is 80r / min, the degassing gas introduced is argon, and the pore size of the plate filter is 38ppi, so as to obtain aluminum liquid with qualified composition;

[0087] S3: Preheat the aluminum liquid with qualified composition and the fresh copper strip on the surface to be used, the preheating temperature is 370°C, and feed them into the roll gap of the twin-roll casting and rolling machine at the same time. Through the high-temperature solid-liquid combination and rolling action, the aluminum material temperature in the casting and rolling zone is 550°C, the billet temperature is 260°C, the casting and rolling reduction is 25%, and the casting and rolling speed is 2.5m / min, so as to obtain a copper-aluminum composite strip billet with a Vickers hardness of 110Hv;

[0088] S4: placing the copper-aluminum composite strip blank in a vacuum protective atmosphere furnace for annealing treatment at a heating temperature of 190° C. for a holding time of 4 hours to obtain an annealed copper-aluminum composite strip;

[0089] S5: cold rolling the annealed copper-aluminum composite strip on a cold rolling mill, with 6 cold rolling passes, a total deformation of 43%, and a single pass deformation controlled at 9%, followed by degreasing and oil removal, acid removal of the oxide layer, and grinding to obtain a finished copper-aluminum composite strip.

[0090] Example 4

[0091] The composition of the copper-aluminum composite material of this embodiment is shown in Table 1, and the performance test results are shown in Table 2, which are as follows:

[0092] S1: The copper strip is alkaline washed to remove oil, and then pickled to remove the surface oxide layer to obtain a fresh surface copper strip for use, the thickness of the copper strip is 3.8 mm, and the Vickers hardness is 66 Hv; the aluminum material is smelted and heat-insulated, the smelting temperature is 740°C, and the heat-insulating temperature is 695°C, and a qualified aluminum liquid is obtained;

[0093] S2: The aluminum liquid with qualified composition is sequentially degassed by a graphite rotor and impurities are removed by a plate filter, and then sent to the casting nozzle through a flow channel. The speed of the graphite rotor is 78r / min, the degassing gas introduced is argon, and the pore size of the plate filter is 30ppi, to obtain aluminum liquid with qualified composition;

[0094] S3: Preheat the aluminum liquid with qualified composition and the fresh copper strip on the surface to be used, the preheating temperature is 390°C, and feed them into the roll gap of the twin-roll casting and rolling machine at the same time. Through the high-temperature solid-liquid combination and rolling action, the aluminum material temperature in the casting and rolling zone is 560°C, the billet temperature is 274°C, the casting and rolling reduction is 18%, and the casting and rolling speed is 3.2m / min, so as to obtain a copper-aluminum composite strip billet with a Vickers hardness of 107Hv;

[0095] S4: placing the copper-aluminum composite strip blank in a vacuum protective atmosphere furnace for annealing treatment at a heating temperature of 200° C. for a holding time of 3 h to obtain an annealed copper-aluminum composite strip;

[0096] S5: cold rolling the annealed copper-aluminum composite strip on a cold rolling mill, with 6 cold rolling passes, a total deformation of 46%, and a single pass deformation controlled at 10%, followed by degreasing and oil removal, acid removal of the oxide layer, and grinding to obtain a finished copper-aluminum composite strip.

[0097] Comparative Example 1

[0098] The composition of the copper-aluminum composite material of this comparative example is shown in Table 1, and the performance test results are shown in Table 2, which are as follows:

[0099] S1: The copper strip is alkaline washed to remove oil, and then pickled to remove the surface oxide layer to obtain a fresh surface copper strip for use, the thickness of the copper strip is 2.8 mm, and the Vickers hardness is 68 Hv; the aluminum material is smelted and heat-insulated, the smelting temperature is 780°C, and the heat-insulating temperature is 720°C, and the smelting qualified aluminum liquid is obtained;

[0100] S2: The aluminum liquid with qualified composition is sequentially degassed by a graphite rotor and impurities are removed by a plate filter, and then sent to the casting nozzle through a flow channel. The speed of the graphite rotor is 40r / min, the degassing gas introduced is argon, and the pore size of the plate filter is 20ppi, so as to obtain aluminum liquid with qualified composition;

[0101] S3: Preheat the aluminum liquid with qualified composition and the fresh copper strip on the surface to be used, the preheating temperature is 500°C, and feed them into the roll gap of the twin-roll casting and rolling machine at the same time. Through the high-temperature solid-liquid combination and rolling action, the aluminum material temperature in the casting and rolling zone is 500°C, the billet temperature is 200°C, the casting and rolling reduction is 22%, and the casting and rolling speed is 2m / min, to obtain a copper-aluminum composite strip billet with a Vickers hardness of 76Hv;

[0102] S4: placing the copper-aluminum composite strip blank in a vacuum protective atmosphere furnace for annealing at a heating temperature of 150° C. for a holding time of 4 h to obtain an annealed copper-aluminum composite strip;

[0103] S5: cold rolling the annealed copper-aluminum composite strip on a cold rolling mill, with 4 cold rolling passes, a total deformation of 50%, and a single pass deformation controlled at 16%, followed by degreasing and oil removal, acid removal of the oxide layer, and grinding to obtain a finished copper-aluminum composite strip.

[0104] Comparative Example 2

[0105] The composition of the copper-aluminum composite material of this comparative example is shown in Table 1, and the performance test results are shown in Table 2, which are as follows:

[0106] S1: The copper strip is alkaline washed to remove oil, and then pickled to remove the surface oxide layer to obtain a fresh surface copper strip for use, the thickness of the copper strip is 3.8 mm, and the Vickers hardness is 64 Hv; the aluminum material is smelted and heat-insulated, the smelting temperature is 800 ° C, and the heat-insulating temperature is 730 ° C, and the smelting qualified aluminum liquid is obtained;

[0107] S2: The aluminum liquid with qualified composition is sequentially degassed by a graphite rotor and impurities are removed by a plate filter, and then sent to the casting nozzle through a flow channel. The speed of the graphite rotor is 100r / min, the degassing gas introduced is argon, and the pore size of the plate filter is 10ppi, so as to obtain aluminum liquid with qualified composition;

[0108] S3: Preheat the aluminum liquid with qualified composition and the fresh copper strip on the surface to be used, the preheating temperature is 200°C, and feed them into the roll gap of the twin-roll casting and rolling machine at the same time. Through the high-temperature solid-liquid combination and rolling action, the aluminum material temperature in the casting and rolling zone is 650°C, the billet temperature is 350°C, the casting and rolling reduction is 25%, and the casting and rolling speed is 5m / min, so as to obtain a copper-aluminum composite strip billet with a Vickers hardness of 69Hv;

[0109] S4: placing the copper-aluminum composite strip blank in a vacuum protective atmosphere furnace for annealing at a heating temperature of 300° C. for a holding time of 2 h to obtain an annealed copper-aluminum composite strip;

[0110] S5: cold rolling the annealed copper-aluminum composite strip on a cold rolling mill, with 6 cold rolling passes, a total deformation of 31%, and a single pass deformation controlled at 6%, followed by degreasing and oil removal, acid removal of the oxide layer, and grinding to obtain a finished copper-aluminum composite strip.

[0111] Comparative Example 3

[0112] This comparative example provides a copper-aluminum composite strip, which is different from Example 1 only in that the content of each element is different, and the rest is the same as Example 1, which will not be repeated here.

[0113] Comparative Example 4

[0114] This comparative example provides a copper-aluminum composite strip, which is different from Example 1 only in that the content of each element is different, and the rest is the same as Example 1, which will not be repeated here.

[0115] Comparative Example 5

[0116] On the basis of Comparative Example 1, the contents of various elements are different, and the others are the same as Comparative Example 1, which will not be repeated here.

[0117] Comparative Example 6

[0118] On the basis of Comparative Example 2, the contents of various elements are different, and the others are the same as Comparative Example 2, which will not be repeated here.

[0119] Comparative Example 7

[0120] This comparative example provides a copper-aluminum composite strip, which is different from Example 1 only in that, during the preparation process of the copper-aluminum composite strip in this comparative example, in step S3, the casting reduction is 10%, the casting speed is 4.0 m / min, and the rest is the same as Example 1 and will not be repeated here.

[0121] Comparative Example 8

[0122] This comparative example provides a copper-aluminum composite strip, which differs from Example 1 only in that, during the preparation process of the copper-aluminum composite strip in this comparative example, in step S3, the casting reduction is 30%, and the casting speed is 2.0 m / min. Other details are the same as Example 1 and will not be repeated here.

[0123] Comparative Example 9

[0124] This comparative example provides a copper-aluminum composite strip, which is different from Example 2 only in that the Fe content in the copper-aluminum composite strip of this comparative example is 25 ppm, and the rest is the same as Example 1, which will not be repeated here.

[0125] Comparative Example 10

[0126] This comparative example provides a copper-aluminum composite strip, which is different from Example 2 only in that the Ni content in the copper-aluminum composite strip of this comparative example is 20 ppm, and the rest is the same as Example 1, which will not be repeated here.

[0127] The element composition of the copper strip in the copper-aluminum composite strip of the embodiment and the comparative example is shown in Table 1:

[0128] Table 1

[0129]

[0130]

[0131] The performance test results of the copper-aluminum composite strips of the embodiment and the comparative example are shown in Table 2:

[0132] Table 2

[0133] Logo Peel strength (N / mm) Combination interface Example 1 38 Uniform Example 2 40 Uniform Example 3 35 Uniform Example 4 37 Uniform Comparative Example 1 30 Uneven Comparative Example 2 28 Uneven Comparative Example 3 23 Uneven Comparative Example 4 15 Uneven Comparative Example 5 10 Uneven Comparative Example 6 12 Uneven Comparative Example 7 22 Uneven Comparative Example 8 28 Uneven Comparative Example 9 26 Uneven Comparative Example 10 31 Uneven

[0134] It can be seen from the above data results that the improvement of the elemental composition of the copper-aluminum composite strip of the present application has a certain synergistic effect on the improvement of the peel strength and bonding interface performance of the copper-aluminum composite strip. By optimizing the elements and their contents, the bonding strength between the copper strip and the aluminum strip and the uniformity of the bonding interface are improved. Specifically, Examples 1 to 4 respectively adopt different process parameters of the present application and produce the copper-aluminum composite strips based on the copper material required by the present application. The peel strength of the copper-aluminum composite strips obtained has reached more than 35N / mm. Although Comparative Examples 1 and 2 use the same copper material as Examples 2 and 3, due to different process parameters, the performance of the copper-aluminum composite strips finally obtained is not as good as that of Examples 1-4, and the bonding interface quality is also uneven. It is considered that the interface quality may be reduced due to a combination of multiple reasons. For example, a higher smelting temperature leads to oxidation and polymerization of aluminum liquid, forming more oxide inclusions, affecting the purity of the aluminum material, and also leading to an increase in pores in the aluminum liquid, affecting the quality of the casting and rolling composite. The decrease in the speed of the graphite rotor and the plate filter with a smaller pore size lead to insufficient degassing of the aluminum liquid and insufficient impurity removal, which further affects the interface performance. The changes in the preheating temperature, the casting temperature and the billet temperature lead to the deterioration of the solid-liquid bonding effect of the copper-aluminum interface, resulting in a weak bonding. Fewer cold rolling passes and a higher deformation amount in a single pass lead to a higher probability of stress concentration problems, and the surface quality of the composite belt is reduced, and surface defects are more likely to occur. The same comparative examples 3 and 4 are compared with examples 1-4 respectively. It can be seen that even if the preparation process is the same, increasing the content of each element can improve the hardness of copper to a certain extent, but the overall negative impact on the performance of the copper-aluminum composite belt is significant. The excessive content of these elements makes the organization of the copper base layer uneven, and may form a brittle phase at the interface, affecting the bonding uniformity and firmness, thereby reducing the mechanical properties and peeling strength of the composite belt. While reducing the content of each element in the preparation of the copper-aluminum composite belt can ensure good interface bonding quality and high peeling strength, but the improvement effect is limited and cannot reach the quality standard of the embodiment of the present application. In Comparative Examples 5 and 6, when the element content and the preparation process are changed at the same time, the bonding performance of the copper-aluminum composite belt finally obtained is significantly reduced, which indirectly proves that there is a certain synergistic effect between the elements and the process in this application. It can be seen from the data of Comparative Examples 7 and 8 compared with Example 1 that by adopting the optimized reduction amount and casting speed, the peel strength of the copper-aluminum composite belt can be significantly improved, and a uniform interface bonding quality can be provided. It can be seen from the comparative data of Comparative Examples 9 and 10 with Example 1 that by properly controlling the sum of the contents of Fe and P, and the sum of the contents of Fe+P+Sn+Ni, it is helpful to improve the peel strength and interface bonding quality of the copper-aluminum composite belt. When the sum of the contents exceeds the corresponding range, it may lead to an increase in impurities and brittle phases, affecting the uniformity and metallurgical bonding degree of the bonding interface, thereby reducing the overall performance of the material.

[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A copper-aluminum composite strip, comprising a composite copper base layer and an aluminum base layer, characterized in that: The copper-based layer is composed of the following elements in weight percentage: 10-30 ppm of Fe, 10-30 ppm of P, 15-30 ppm of Sn, 10-20 ppm of Ni and the balance of Cu; the aluminum-based layer is composed of the following elements in weight percentage: 99.0-99.9% of Al and the balance of inevitable impurities.

2. The copper-aluminum composite strip according to claim 1, characterized in that In the copper-based layer, the total content of Fe and P is 20-50 ppm, and the total content of Fe, P, Ni and Sn is 45-85 ppm.

3. The method for preparing the copper-aluminum composite strip according to any one of claims 1 to 2, characterized in that: The steps include: Step 1: The copper strip is subjected to alkaline washing to remove oil and acid washing to remove the oxide layer, so as to obtain a copper strip with a fresh surface for use; the aluminum material is smelted and heat-insulated to obtain aluminum liquid; Step 2, the aluminum liquid is sequentially degassed by a graphite rotor and impurities are removed by a plate filter, and then sent to a casting nozzle through a flow channel to obtain aluminum liquid to be used; Step 3: preheat the aluminum liquid and the copper strip to be used, and feed them into the roll gap of the twin-roll casting machine at the same time, and obtain the copper-aluminum composite strip billet under the action of high-temperature solid-liquid combination and rolling; Step 4: placing the copper-aluminum composite strip blank in a vacuum atmosphere protection furnace for annealing to obtain an annealed copper-aluminum composite strip; Step 5: cold rolling the annealed copper-aluminum composite strip on a cold rolling mill, followed by degreasing and oil removal, acid removal of the oxide layer, and grinding to obtain a finished copper-aluminum composite strip.

4. The method for preparing the copper-aluminum composite strip according to claim 3, characterized in that: In step 1, the thickness of the copper strip is 2.8-3.8 mm, and the Vickers hardness of the copper strip is 64-70 Hv.

5. The method for preparing the copper-aluminum composite strip according to claim 3, characterized in that: In step 1, the aluminum material is smelted at a temperature of 700-750°C and held at a temperature of 680-700°C.

6. The method for preparing the copper-aluminum composite strip according to claim 3, characterized in that: In step 2, the rotation speed of the graphite rotor is 60-80 rpm, and / or; the degassing gas introduced into the graphite rotor is argon, and / or; the pore size of the plate filter is 30-50 ppi.

7. The method for preparing the copper-aluminum composite strip according to claim 3, characterized in that: In step three, the preheating temperature of the copper strip is 350-400°C, and / or; the aluminum material temperature in the casting and rolling zone is 550-600°C, and / or; the billet discharge temperature is 260-280°C, and / or; the casting and rolling reduction is 15-25%, the casting and rolling speed is 2.5-3.5m / min, and / or; the Vickers hardness of the copper side of the copper-aluminum composite strip is 100-110Hv.

8. The method for preparing the copper-aluminum composite strip according to claim 3, characterized in that: In step 4, the heating temperature of the copper-aluminum composite strip is 190-240° C., and the insulation time is 2-4 hours.

9. The method for preparing the copper-aluminum composite strip according to claim 3, characterized in that: In step 5, the annealed copper-aluminum composite strip is cold-rolled for 6 times, with a total deformation of 39-50%, and a single-pass deformation controlled at 8-11%.

10. The method for preparing the copper-aluminum composite strip according to claim 3, characterized in that: The peel strength of the finished copper-aluminum composite strip is 35-40N / mm.